The relationship between a satisfactory in-store shopping experience and retailer loyalty - N. S. Terblanche; C. Boshoff (South African Journal of Business Management, 2006)
In this study consumer satisfaction with the in-store shopping experience is used to predict two measures of retailer loyalty. The first measure is an attitudinal measure of loyalty. The second measure is actual buying behaviour – actual sales recorded in monetary terms and in terms of units bought. The results suggest that a satisfactory in-store shopping experience enhances cumulative or `overall' consumer satisfaction, which in turn enhances both attitudinal loyalty and behavioural loyalty (actual sales).
Keywords: 650